Incidence and Risk Factors of Stroke-Associated Pneumonia in Ischemic Stroke with Dysphagia: A Cross-Sectional Study - Sukiandra, Riki; Maryanti, Yossi; Sucipto; Juananda, Desby; Trihardi, Rizfan; Risman, Salsa Wiratama; Qadriyyah, Lu’lu’ul; Ashiddiqi, Hafil (Rumah Sakit Umum Pusat (RSUP) Dr. M. Djamil, 2025)
Background: Stroke-associated pneumonia (SAP) is a common and debilitating complication following stroke, typically occurring within the first 7 days of onset in about one-third of patients with acute ischemic stroke. SAP significantly contributes to increased morbidity, mortality, and healthcare costs due to prolonged hospitalizations. In Riau, the reported prevalence of stroke is 8.3%, which has been rising since 2013, alongside an increase in SAP cases. Dysphagia, defined as difficulty swallowing, is a major risk factor for SAP as it predisposes patients to aspiration, a leading cause of pneumonia. If left untreated, dysphagia can lead to dehydration and electrolyte imbalance. Despite the clinical importance of SAP, local data regarding its incidence and associated risk factors at Arifin Achmad General Hospital in Riau Province is lacking. This study aims to investigate the incidence and risk factors associated with SAP in ischemic stroke patients with dysphagia. The findings are expected to provide evidence-based references to improve neurointensive care and preventive strategies for SAP in this patient population. Methods: This cross-sectional study was conducted at Arifin Achmad General Hospital, Riau Province, from August to November 2023. Ischemic stroke patients who underwent the Water Swallow Test (WST) were included. Dysphagia, electrolyte imbalance, and SAP were the key variables. Data were collected from medical records and observation sheets. Statistical analysis was performed using the Chi-square test (p < 0.05) with SPSS version 25. Results: The study found that 37.5% (15 patients) of ischemic stroke patients developed stroke-associated pneumonia, while 42.5% experienced dysphagia. The majority of these patients were aged 51-60 years (41.2%), male (58.8%), had their first stroke attack (60%), and had multiple risk factors (73.3%). A significant number of dysphagia patients had low electrolyte levels. The most common lesion locations in dysphagia patients were bilateral (66.7%). There was a significant correlation between dysphagia and the incidence of SAP (p=0.000). Patients with dysphagia had 78.75 times higher odds of developing SAP (95% CI: 9.95-622.6) compared to those without dysphagia. Conclusion: SAP is a frequent complication in ischemic stroke patients. Future prospective studies should adopt a unified definition, strict inclusion criteria, and long-term follow-up to better identify the incidence, prognosis, and related factors of SAP.